An Administrative-Military Headquarter During the Reign of Mahmud II: Rami Barracks - (:unkn) unknown (ISTANBUL 29 MAYIS UNIV & ISAM, 2018)
This essay examines the process of transition in the Ottoman military system from Janissary chambers to barrack structures, built for the modern trained regular armies on the European model. In this context, the main focus will be on the construction of the Rami Ciftlik Barrack, which is built for newly established Asakir-i Mansure Army after the Auspicious Event (Vak'a-i Hayriyye) in 1826; also to protect Mahmud II himself from counter-coup attempts of annihilated Janissary corps remaining's. The steps also were taken by Mahmud II to calm the public tension and raising morale of army, fighting against the Russia which is broke out in 1828. The essay analyzes, on the other hand, assuring attempts of Mahmud II against far opposition circles which criticize his radical reforms harshly, also his official acts and everyday life activities in Rami Barrack which he resided 617 days; Meanwhile, the essay tried to evaluate main events that played role in becoming Rami Barrack an interim administrative and military base; likewise important developments occurred in the history of the Rami Barracks after the era of Mahmud II till today.
Keywords: Barracks; Janissaries; Rami Barrack; Davudpasa Barrack; Ottoman Architecture; Mahmud II; Asakir-i Mansure Army